PENGARUH GLOBALISASI PELAKSANAAN HARI RAYA NYEPI DALAM BALI KEKINIAN - I Made Arka (Jurnal Ilmiah Cakrawarti, 2021)
The implementation of Nyepi is held every year. All Hindu communities make preparations in the implementation, but in its implementation in each region, Hindus welcome differences in understanding and activity in the contemporary Bali, influenced by globalization. If seen from the meaning of Nyepi, Nyepi comes from a lonely word, which means quiet, silent, loose, no activity. Then Nyepi is a Hindu New Year based on the Saka calendar / calendar, which began in 78 AD. Unlike the celebration of the new year (every January 1), the Saka New Year in Bali begins with seclusion and carrying out the chess collection, which includes among others; (1) Observe Geni (may not turn on the fire), (2) Observe the Work (may not work), (3) Observe the Surge (may not travel out of the house), (4) Observe Lelanguan (may not carry out entertainment). In this study there are several formulation of the problem discussed by the author to obtain information and procedures in the series of implementation of Settlement Brata Chess.